Analisis Pengendalian Persediaan Bahan Baku dengan Metode Economic Order Quantity (EOQ) : Studi Kasus pada Konveksi Rizar Collection Periode Tahun 2021 - Erik Ridwan; Suci Putri Lestari; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
The pupose of this study is to find out how the implementation of material inventory control that has been carried out at Rizar Collection convection, how to apply the Economic Order Quantity (EOQ) method in controlling raw material inventory at Rizar Collection convection. Data collection techniques in this study is to use interview techniques, library research and observation. The method used in this study is a analytical descriptive method. The analytical tool used is the Economic Order Quantity (EOQ), Safety Stock, ReOrder Point, and Total Inventory Cost method. Based on the results of the study, it is known that the calculation of the Economic Order Quantity (EOQ) method shows that the total cost of raw material inventory that must be issued by the company is greater than the total inventory cost calculated using the Economic Order Quantity (EOQ) method. Companies should follow the calculation of the Economic Order Quantity (EOQ) method so that they can save on raw material inventory costs, optimize inventory and streamline inventory costs.